2019
DOI: 10.3762/bjnano.10.91
|View full text |Cite
|
Sign up to set email alerts
|

The systemic effect of PEG-nGO-induced oxidative stress in vivo in a rodent model

Abstract: Oxidative stress (OS) plays an important role in the pathology of certain human diseases. Scientists have developed great interest regarding the determination of oxidative stress caused after the administration of nano-graphene composites (PEG-nGO). Graphene oxide sheets (GOS) were synthesized via a modified Hummer's method and were characterized by X-ray diffraction (XRD), ultraviolet–visible spectroscopy (UV), and transmission electron microscopy (TEM). The method of Zhang was adopted for cracking of GOS. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 54 publications
8
75
0
Order By: Relevance
“…On the basis of X‐ray diffraction (XRD), as shown in Figure 2b, it can be concluded that all samples are basically X‐ray amorphous, and only for FeNC phen a small diffraction peak at 2 θ = 26.6° related to the graphite (002) crystal phase was detected after prolonged data acquisition. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of X‐ray diffraction (XRD), as shown in Figure 2b, it can be concluded that all samples are basically X‐ray amorphous, and only for FeNC phen a small diffraction peak at 2 θ = 26.6° related to the graphite (002) crystal phase was detected after prolonged data acquisition. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…A sharp peak at around 1725 cm −1 , which is assigned to C=O stretching vibrations, demonstrated the presence of carbonyl and carboxyl groups [ 30 , 39 ]. An absorption band at ≈1616 cm −1 appears owing to the stretching of cyclic alkene (C=C) from unoxidized graphitic domain [ 30 , 40 , 41 ]. Additionally, the presence of ethers is evidenced by the appearance of strong absorption bands at around 1160 cm −1 and 1040 cm −1 , which are assigned to C−O stretching vibrations, and through epoxides exhibiting C−O bending vibrations at around 878 cm −1 [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A peak was evident at around 1725 cm −1 in both GO and GOn spectra, which is assigned to C=O stretching vibrations, demonstrating the presence of carbonyl and carboxyl groups [ 3 , 14 , 20 ]. The stretching of cyclic alkene (C=C) was observed at approximately 1610 cm −1 , which results from the unoxidized graphitic backbone [ 20 , 21 , 22 ]. C−O stretching vibrations attributed to ethers were present at around 1140 and 1020 cm −1 , and C−O bending vibrations of epoxides were found at around 858 cm −1 [ 3 , 14 ].…”
Section: Resultsmentioning
confidence: 99%